THE ROLE OF LANGUAGE GAMES IN DEVELOPING LINGUISTIC ABILITIES - Mavluda Abduvaliyevna Komiljonova (European Science Publishing, 2024)
The article reveals on the notion of the language game as a form of linguistic abilities and the creation of conditions for the development of students’ creative abilities. The manifestation of these skills is the formation of new words and the willingness to choose the stylistic devices.
Keywords: language game, creativity, linguistic creativity, linguistic intelligence, language creation.